Patterns of infections, aetiological agents and antimicrobial resistance at a tertiary care hospital in northern Tanzania. Issue 4 (3rd February 2017) - Kumburu, Happiness Houka; Sonda, Tolbert; Mmbaga, Blandina Theophil; Alifrangis, Michael; Lund, Ole; Kibiki, Gibson; Aarestrup, Frank M.
Abstract: Objective: To determine the causative agents of infections and their antimicrobial susceptibility at a tertiary care hospital in Moshi, Tanzania, to guide optimal treatment. Methods: A total of 590 specimens (stool (56), sputum (122), blood (126) and wound swabs (286)) were collected from 575 patients admitted in the medical and surgical departments. The bacterial species were determined by conventional methods, and disc diffusion was used to determine the antimicrobial susceptibility pattern of the bacterial isolates. Results: A total of 249 (42.2%) specimens were culture‐positive yielding a total of 377 isolates. A wide range of bacteria was isolated, the most predominant being Gram‐negative bacteria: Proteus spp. ( n = 48, 12.7%), Escherichia coli ( n = 44, 11.7%), Pseudomonas spp. ( n = 40, 10.6%) and Klebsiella spp ( n = 38, 10.1%). Wound infections were characterised by multiple isolates ( n = 293, 77.7%), with the most frequent being Proteus spp. ( n = 44, 15%), Pseudomonas ( n = 37, 12.6%), Staphylococcus ( n = 29, 9.9%) and Klebsiella spp. ( n = 28, 9.6%). All Staphylococcus aureus tested were resistant to penicillin ( n = 22, 100%) and susceptible to vancomycin. Significant resistance to cephalosporins such as cefazolin ( n = 62, 72.9%), ceftriaxone ( n = 44, 51.8%) and ceftazidime ( n = 40, 37.4%) was observed in Gram‐negative bacteria, as well as resistance to cefoxitin ( n = 6, 27.3%) in S. aureus . Conclusion: The study has revealed a wide range of causative agents, with an alarming rate of resistance to the commonly used antimicrobial agents. Furthermore, the bacterial spectrum differs from those often observed in high‐income countries. This highlights the imperative of regular generation of data on aetiological agents and their antimicrobial susceptibility patterns especially in infectious disease endemic settings. The key steps would be to ensure the diagnostic capacity at a sufficient number of sites and implement structures to routinely exchange, compare, analyse and report data. Sentinel sites (hospitals) across the country (and region) should report on a representative subset of bacterial species and their susceptibility to drugs at least annually. A central organising body should collate the data and report to relevant national and international stakeholders.